You have two exponential functions. One function has the formula g(x) = 3(2 x ). The other function has the formula h(x) = 2 x+1. Which option below gives formula for k(x) = (g – h)(x)? A) k(x) = 2x B) k(x) = 5(2x) C) k(x) = 5(2x+1) D) k(x) = 2

QUESTION POSTED AT 29/05/2020 - 01:06 AM

Answered by admin AT 29/05/2020 - 01:06 AM

Given two exponential functions:
g(x)=3(2^x) and h(x)=2^{x+1}

k(x) = (g-h)(x) is given by
k(x)=g(x)-h(x) \\  \\ =3(2^x)-2^{x+1}=3(2^x)-2(2^{x}) \\  \\ =2^x(3-2)=2^x

Therefore, the option that gives the formula for k(x) = (g - h)(x) is option A.
k(x)=2^x
Post your answer

Related questions

The expression 3 × 7 – 4 × 8 + 2 is equivalent

QUESTION POSTED AT 02/06/2020 - 01:42 AM

Graph the exponential function. y = 4(3) x

QUESTION POSTED AT 02/06/2020 - 01:30 AM